Ambidexterity and Perceived Organizational Support Predict Employee Performance: Roles of Dark Triad and Job Satisfaction - Yokanan, Raden Teja; Nazara, Mardin (MATRIK: JURNAL MANAJEMEN, STRATEGI BISNIS, DAN KEWIRAUSAHAAN, 2026)
In today’s competitive business environment, organizations must balance exploitation and exploration to sustain employee performance. This study examines the effects of ambidexterity, perceived organizational support (POS), job satisfaction, and the Employee Dark Triad on employee performance. Using a quantitative approach, data were collected from 150 employees of PT Nutrisi Keluarga, Indonesia, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that ambidexterity and job satisfaction positively affect employee performance, while POS significantly enhances job satisfaction, which mediates its relationship with performance. Furthermore, the Employee Dark Triad shows a positive direct effect on performance but negatively moderates the relationship between ambidexterity and performance. This study contributes to the human resource management literature by developing a moderated–mediation model integrating organizational capabilities, support mechanisms, and personality traits. Practically, organizations should foster ambidexterity, strengthen organizational support, promote job satisfaction, and manage dark personality tendencies to optimize employee performance.